Price instability in multi-unit auctions - Edward Anderson; Pär Holmberg (Research Institute of Industrial Economics (IFN), 2015)
We consider a procurement auction, where each supplier has private costs and submits a stepped supply function. We solve for a Bayesian Nash equilibrium and show that the equilibrium has a price instability in the sense that a minor change in a supplier.s cost sometimes result in a major change in the market price. In wholesale electricity markets, we predict that the bid price of the most expensive production unit can change by 1-10% due to price instability. The price instability is reduced when suppliers have more steps in their supply functions for a given production technology. In the limit, as the number of steps increases and the cost uncertainty decreases, the Bayesian equilibrium converges to a pure-strategy NE without price instability, the Supply Function Equilibrium (SFE).
Keywords: C62; C72; D43; D44; L94; 330; Multi-unit auctions; indivisible unit; price instability; Bayesian Nash equilibria; supply function equilibria; convergence of Nash equilibria; whole-sale electricity markets